Pengaruh Gaya Kepemimpinan Demokratis, Motivasi Kerja dan Lingkungan Kerja Terhadap Kinerja Karyawan Pada PT. Matahari Department Store Grand Mall Bekasi (Sekolah Tinggi Ilmu Ekonomi Mulia Pratama, 2023)
Human resources are a central factor in managing an organization. The achievement of an organization requires human resources as system managers. Competent human resources with good performance can support business success. Incompetent and underperforming human resources are a competitive problem that can put the company in a loss-making condition. Pt. Matahari Department Store Grand Mall Bekasi, is a retail company in Indonesia that is very competent in creating human resources who have good performance and support the success of the company. In SPSS 26 used by the researcher, with the results of multiple linear analysis tests with regression coefficient values so as to get the equation model as follows: Y = a + b1X1 + b2X2 + b3X3 which means Y = 4.963 + 0.229 X1 + 0.263 X2 + 0.465 X3. The results of the test for the coefficient of determination (R2) with a coefficient of determination (????2) is 0.757 or 75.7% of employee performance variables can be explained by the three independent variables. The results of the t statistical test with a comparison of the calculated t value with the t table on the variable. t table value of 1,999. Because the calculated t value of X1 = 2.588 and X3 = 3.067 is greater than > t table 1.999, then HO is rejected and H1 is accepted, which means that partially states